Childfree Problems And Their Solutions From An Islamic Perspective - Nailis Shofita; Raushani Azza; Syahrozad Khunaifah (Eduvest - Journal of Universal Studies, 2021)
Recently, there has been a child-free phenomenon that is being discussed, especially in Indonesia. It causes various questions regarding the views of the pros and cons of childfree itself, then how does Islam respond to it? What are the childfree problems and their solutions from Islamic view? Islam is one of the religions that can answer current problems based on the Al-Quran and Sunnah. As the basis of religion, the Qur'an and the sunnah have discussed many child-free problems.  Therefore, this study is aimed to determine the problem of childfree and its solution in the view of Islam . This research used the Library Research method or literature review with a qualitative research approach.  The results of this study, in the view of Islam, married couples who choose child-free include acts that are against nature because having children is a blessing and as human nature. Islam also responds to child freedom with several arguments about the primacy  of kids in the family.